EVALUASI IMPLEMENTASI PROGRAM NEIGHBORHOOD UPGRADING AND SHELTER PROJECT PHASE 2 (NUSP-2) DI KOTA BANDAR LAMPUNG (STUDI KASUS: KELURAHAN KOTA KARANG RAYA KECAMATAN TELUK BETUNG TIMUR) - Farhan Nailal Umam; Nia Kurniasih Pontoh; Mia Ermawati (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
One form of implementation of the mandate of the Law of the Republic of Indonesia No. 1 of 2011 concerning Housing and Settlement Areas is explicitly stated in the Presidential Regulation of the Republic of Indonesia No. 2 of 2015 concerning the National Medium Term Development Plan for 2015-2019 and implemented in the form of Kep. Director of DJCK No. 110/KPTS/DC/2016 concerning Determination of City Locations Without Slums. The decision of the Directorate General of Human Settlements became the basis for determining the location of the area that was determined to receive a program to improve the quality of slums, one of which was the NUSP-2 program. NUSP-2 as one of the slum settlement programs needs to be evaluated as a form of assessing the results of the programs that have been implemented. The evaluation carried out focused on the impact side with the scope of Physical and Non-Physical (Social and Economic) impacts and sustainability with the scope of economic, social/community and environmental sustainability, where the impact evaluation resulted in a value of 0.692 or was in the moderately impactful class, while the sustainability evaluation was at a value of 0.692. 0.43 or is in the less sustainable class. However, what is of concern is that based on the results of the analysis carried out, the side that has a large influence on the evaluation value is the side that is in direct contact with the NUSP-2 program, with examples for evaluation of physical impacts having a greater influence than non-physical and social sustainability having the greatest influence compared to sustainability environment and economy.